Effect of alcohol on liver enzyme (sGOT) (Journal of the College of Basic Education, 2023)
This study was aimed to estimated effect of alcohol on liver enzyme (GOT) , long term alcohol consumption can cause alcoholic liver disease It leads to develope alcoholic hepatitis and cirrhosis, Most of the liver damage caused by alcohol is attributed to alcohol metabolism and by products of that metabolism, Liver injury may be caused by direct toxicity of alcohol by products and also by inflammation that is induced secondarily by these same compounds, One half of heavy drinkers develop alcoholic hepatitis or cirrhosis